Identification of Function Groups of Ethanol Extract and n-Hexane Extract of Coriander Seeds (Coriandrum sativum) Using Infrared Spectrophotometer - Dhina Ayu Susanti; Lindawati Setyaningrum (UrbanGreen, 2020)
Coriander (Coriandrum sativum) is a popular spice plant in Indonesia. Some active compounds contained in coriander seeds can be used as natural analgesics. This study aims to identify the functional groups contained in coriander seed extract. The solvent used to make coriander seed extract is ethanol and n-hexane, while the extraction method uses sohxlet. The extract obtained was then identified by its functional group using an Infrared spectrophotometer. The results of the identification of functional groups in the ethanol extract of coriander seeds showed some uptake that appeared at a wavelength of 3371.29 cm-1; 2923.59 cm-1; 2853.95 cm-1; 1583.22 cm-1; 1400.71 cm-1, and 1074.80 cm-1. The results of the identification of functional groups in the n-Hexane extract of coriander seeds showed some uptake that appeared at wavelengths of 2923.32 cm-1; 2853.41 cm-1; 1745.36 cm-1; 1461.9 cm-1; 1376.54 cm-1, 1161.67 cm-1, and 919.32 cm-1.